REORIENTASI KURIKULUM PENDIDIKAN PESANTREN - Mundir (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
Pesantren (Islamic Boarding School) with a typical education more focused on religious subjects (diniyyah) is the oldest religion and religious education in indonesia. From the side of innovation, found some Pesantren innovation that will still do, innovation was doing , and has been an invasion .This innovation has touched on some aspects, ranging from education curriculum, kiyai leadership style, santri daily way of life, dormitory buildings, the mosque, kiyai house, kiyai vehicles, a model of learning , learning strategy, until the management of funds. But this article limiting discuss about education curriculum on aspects of innovation, in modern and traditional models.